2005
DOI: 10.1161/circulationaha.105.536169
|View full text |Cite|
|
Sign up to set email alerts
|

Prednisolone Inhibits Proliferation of Cultured Pulmonary Artery Smooth Muscle Cells of Patients With Idiopathic Pulmonary Arterial Hypertension

Abstract: Background-Idiopathic pulmonary arterial hypertension (IPAH) is associated with proliferation of smooth muscle cells (SMCs) in small pulmonary arteries. There is no therapy that specifically inhibits SMC proliferation. Recent studies reported that prednisolone (PSL) inhibits the postangioplasty proliferation of SMCs in atherosclerotic arteries. In this study, we tested the hypothesis that PSL has antiproliferative effects on pulmonary artery SMCs of patients with IPAH. Methods and Results-Pulmonary artery SMCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 29 publications
(29 reference statements)
5
60
0
Order By: Relevance
“…The antiproliferative findings in this study are consistent with a study of prednisolone on platelet-derived growth factor-stimulated PASMCs from PAH patients [47], although that study used much higher doses (equating to 3610 -5 and 3610 -4 M dexamethasone).…”
Section: Discussionsupporting
confidence: 89%
“…The antiproliferative findings in this study are consistent with a study of prednisolone on platelet-derived growth factor-stimulated PASMCs from PAH patients [47], although that study used much higher doses (equating to 3610 -5 and 3610 -4 M dexamethasone).…”
Section: Discussionsupporting
confidence: 89%
“…When a vasoconstrictive or mitogenic ligand binds with its receptor in the plasma membrane in PASMC, a rise in [Ca 2ϩ ] cyt due to Ca 2ϩ release and/or entry is an important signaling mechanism for agonist-mediated PASMC contraction and mitogen-mediated PASMC proliferation. Compared with PASMC from normal subjects, many studies have demonstrated that 1) the proliferation rate (determined by cell number, DNA content, and 3 H-thymidine incorporation) is significantly accelerated (37,38,59) and 2) the store depletion-mediated Ca 2ϩ entry is enhanced in PASMC from IPAH patients (59), as well as in PASMC from chronically hypoxic animals (32,57). Therefore, PASMC from IPAH patients may undergo phenotypic changes that make the cells more prone (inclined) to proliferation and contraction or to activation by contractile agonists and mitogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Ogawa and coworkers reported an immunosuppressant, prednisolone, to have an antiproliferative effect on cultured SMC of pulmonary arteries from patients with idiopathic PAH, thus suggesting that prednisolone may be potentially useful therapeutically in patients with idiopathic PAH (82). Moreover, they have shown that PDGF-induced nuclear translocation of NF-kB may play an important role in stimulating pulmonary arterial SMC proliferation (and/or enhancing pulmonary arterial SMC survival), whereas prednisolone may exert both anti-inflammatory and antiproliferative effects on PASMC by inhibiting NF-kB nuclear translocation (83).…”
Section: The Role Of Immunitymentioning
confidence: 99%